The Impact of Texting on Perceptions of Face-to-Face Communication in Couples in Different Relationship Stages. Issue 4 (1st October 2016) - Novak, Joshua R.; Sandberg, Jonathan G.; Jeffrey, Aaron J.; Young-Davis, Stephanie
Abstract : The authors examine both actor and partner effects of the use of texting on face-to-face communication behaviors in three groups: dating couples (n = 1, 217), engaged couples (n = 2, 167), and married couples (n = 1, 336). Data were taken from the RELATE project (www.relateinstitute.org ). Overall, the more an individual used texting to discuss serious issues, broach confrontational subjects, and apologize, the more conflictual face-to-face communication behaviors existed for both themselves and their partners. Similar partner effects were found. When couples used texting to express affection, the less conflictual face-to-face communication behaviors existed for both partners. Clinical implications will be discussed.